A novel frameshift variant in ALS2 associated with segmental axonopathy in Merino sheep - Eager KLM; Jolly RD; Manning L; Willet CE; Snell RG; Lehnert K; Mckean NE; Sneddon NW; O’Rourke BA; Dittmer KE; Tammen I; Littlejohn M (BioMed Central Ltd, 2025)
Background: Segmental axonopathy is a recessively inherited neurodegenerative disorder that has affected Merino sheep since the early 1930s. Despite its long-standing recognition, the genetic basis of the condition remained unknown. This study aimed to identify the genetic cause of segmental axonopathy and confirm its pathological features to improve diagnostic accuracy and inform breeding strategies. Results: Whole genome sequencing and genotyping of affected and unaffected Merino sheep identified a novel homozygous frameshift variant in the ALS2 gene that segregated with disease. RNA sequencing of cerebellar peduncle tissue confirmed the nonsense consequence on the ALS2 transcript. Histological analysis highlighted the hallmarks of the disease as large, foamy eosinophilic axonal swellings predominantly in the trigeminal ganglia, with additional degenerative changes in both the brain and spinal cord. These findings support the value of targeted sampling of sensory roots of the trigeminal nerve, spinal cord tracts, and dorsal nerve rootlets to enhance diagnostic accuracy. The same ALS2 variant was found across multiple unrelated flocks in both Australia and New Zealand, indicating a broader presence within the fine-wool Merino sheep population. Conclusions: This study identifies a novel ALS2 frameshift variant associated with segmental axonopathy in Merino sheep and provides both genetic and histological evidence supporting its role in disease pathology. The development of a DNA diagnostic test will enable more informed breeding decisions, reduce the prevalence of this condition, and improve animal welfare and productivity in the Merino industry. Moreover, the findings offer a potential large-animal model for exploring early-onset forms of human motor neuron diseases, including amyotrophic lateral sclerosis, in which ALS2 variants are implicated.